Pengaruh Pola Asuh Orang Tua terhadap Akhlak Mahasiswa PAI FIAI UII: Perbandingan Antara Pendidikan Pesantren dan Non-Pesantren - Aisa, Dewi; Ghazali, Raisul Umam (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
This research is motivated by the phenomenon of differences in moral character among students with pesantren and non-pesantren educational backgrounds, as well as the crucial role of parenting styles in shaping moral character. The study aims to explore the influence of parenting styles on the moral character of PAI FIAI UII students from the 2016 cohort, comparing groups with pesantren and non-pesantren backgrounds. The research method employs a quantitative approach with a descriptive correlational and comparative analysis design. The sample consists of 110 students selected through quota sampling. Data collection utilizes a Likert scale questionnaire and is analyzed using simple linear regression. Results indicate that parenting styles have a positive and significant influence on students' moral character in both groups, with a stronger influence on the pesantren background group (52.4%) compared to the non-pesantren group (47.9%). Keywords: parenting style, student moral character, pesantren, higher education